2019
DOI: 10.1111/anu.12958
|View full text |Cite
|
Sign up to set email alerts
|

Pectic hydrolysates in the diet of silver catfish (Rhamdia quelen): Growth performance, blood and liver biochemistry, histological parameters and intestinal contents

Abstract: The aim of this study was to investigate the prebiotic potential of pectin hydrolysates that were extracted from agroindustrial waste (apple pomace—AP and passion fruit peel—PFP) and were added to the diet of silver catfish (Rhamdia quelen). A 49‐day biological assay was conducted, and five test diets were evaluated: one diet was a control diet and the other four diets included pectin hydrolysates (2.5 and 5 g/kg). At 49 experimental days, biometric data and biological material were collected to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…The reduction of 4% of the CP level without AA supplementation did not influence intestinal morphological changes. Silver catfish fed by‐products not resulted in changes in the height of intestinal villi and showed good growth (Mombach et al., 2019). Some studies have reported intestinal changes in fish fed with AA supplementation in the diet (Cai et al., 2018; Gao et al., 2019; Ostaszewska et al., 2011; Zhou et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of 4% of the CP level without AA supplementation did not influence intestinal morphological changes. Silver catfish fed by‐products not resulted in changes in the height of intestinal villi and showed good growth (Mombach et al., 2019). Some studies have reported intestinal changes in fish fed with AA supplementation in the diet (Cai et al., 2018; Gao et al., 2019; Ostaszewska et al., 2011; Zhou et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Em outro trabalho com hidrolisados para jundiás foi observado ainda, maior contagem de células caliciformes. Esse aumento indica uma maior proteção, renovação celular e integridade epitelial, ou seja, melhor saúde intestinal dos animais suplementados (Mombach et al, 2019).…”
Section: Rhamdia Quelenunclassified